2012
DOI: 10.4236/fns.2012.33054
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Concentrations of Dietarily-Important Trace Elements and Macronutrients in Edible Leaves and Grain of 27 Cowpea (<i>Vigna unguiculata</i> L. Walp.) Genotypes: Implications for Human Nutrition and Health

Abstract: Legumes are a good source of calories, protein and mineral nutrients for human nutrition and health. In this study, the edible leaves and grain of 27 field-grown cowpea genotypes were assessed for trace elements and macronutrient density at Manga in the Sudano-Sahelian zone of Ghana in 2005 and 2006, using inductively coupled plasma-mass spectrometry. The genotypes differed markedly in their accumulation of trace elements and major nutrients in edible leaves and grain. Except for P, the concentrations of K, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
2
13
0
1
Order By: Relevance
“…Interestingly, the leaves of cowpea genotypes Apagbaala, Line 2020, Iron Gray, IT94D-437-1, and Omondaw were similarly very rich in Mn and B, as found for Fe and Zn. These results agree with the findings of Belane and Dakora (2012), and suggest that, with little effort, breeders can easily identify cowpea genotypes with the ability to accumulate high levels of the micronutrients Fe, Zn, Mn, and B in edible leaves for use by farmers to overcome trace element deficiency in Africa.…”
Section: Trace Element Density In Cowpea Leaves and Seedssupporting
confidence: 89%
“…Interestingly, the leaves of cowpea genotypes Apagbaala, Line 2020, Iron Gray, IT94D-437-1, and Omondaw were similarly very rich in Mn and B, as found for Fe and Zn. These results agree with the findings of Belane and Dakora (2012), and suggest that, with little effort, breeders can easily identify cowpea genotypes with the ability to accumulate high levels of the micronutrients Fe, Zn, Mn, and B in edible leaves for use by farmers to overcome trace element deficiency in Africa.…”
Section: Trace Element Density In Cowpea Leaves and Seedssupporting
confidence: 89%
“…Muchoki et al (2010) reported a reduction of 71.9% in the nitrate content of cowpea vegetables subjected to fermentation. The overall aim of the fermentation process has been to improve on the shelf-life of the cowpea leaves, while at the same time the nutritional quality has also been improved.…”
Section: Fermentationmentioning
confidence: 99%
“…Cowpea leaves have antinutritional factors such as oxalates, phytates, and nitrates which are known to have negative impact on the nutrient intake of individuals (Muchoki et al, 2010;Oulai, Zoue, & Niamke, 2015). Optimal processing and preservation techniques should seek to reduce or minimize the accumulation of these antinutritional factors as a way of ameliorating the nutritional quality.…”
Section: Antinutritional Factors In Cowpea Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to variations in legume symbiotic performance resulting from genotypic differences and N 2 -fixing efficiency of the rhizobial symbionts, there is often the need to screen for improved N 2 fixation among legume germplasm [6] [7]. Of the many techniques used to estimate legume symbiotic performance, the 15 N natural abundance has so far been useful in quantifying N 2 fixation in field-grown legumes [8] [9]. This technique requires the estimation of the isotopic fractionation associated with N 2 fixation in the legume (so called B value), and the selection of reference plants to estimate the soil N uptake by the legume [10] [11].…”
Section: Introductionmentioning
confidence: 99%